2022
DOI: 10.3390/cancers14174325
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for Cancer Treatment during Pregnancy: Ethics-Related Content Evolution and Implications for Clinicians

Abstract: (1) Background: Current scientific evidence suggests that most cancers, including breast cancer, can be treated during pregnancy without compromising maternal and fetal outcomes. This, however, raises questions regarding the ethical implications of clinical care. (2) Methods: Using a systematic literature search, 32 clinical practice guidelines for cancer treatment during pregnancy published between 2002 and 2021 were selected for analysis and 25 of them mentioned or made references to medical ethics when offe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 54 publications
(105 reference statements)
0
14
0
Order By: Relevance
“…A recent review identifying ethical concepts covered in the treatment guidelines for CDP found patient autonomy dominated [ 32 ]. While relational autonomy—the involvement of the partner and or family in decision-making—was included within this principle, reference to relational autonomy was only found in 10 of the 25 included guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review identifying ethical concepts covered in the treatment guidelines for CDP found patient autonomy dominated [ 32 ]. While relational autonomy—the involvement of the partner and or family in decision-making—was included within this principle, reference to relational autonomy was only found in 10 of the 25 included guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Ethical questions raised by the healthcare team, patients and/or their families are not always the same and might be conflicting, such as when one party does not feel comfortable with care decisions that are either taken or desired by another party involved [33,34]. For these reasons, taking care of pregnant cancer patients requires a multidisciplinary clinical team that should also include decisional counsellors [35,36], psychologists and ethicists [37], in addition to the oncological core medical team [1,[38][39][40].…”
Section: Relationship Between Pregnancymentioning
confidence: 99%
“…Ethical questions raised by the health patients and/or their families are not always the same and might be conflicti when one party does not feel comfortable with care decisions that are either ta sired by another party involved [33,34]. For these reasons, taking care of pregn patients requires a multidisciplinary clinical team that should also include counsellors [35,36], psychologists and ethicists [37], in addition to the oncol medical team [1,[38][39][40]. To provide patient-centric, ethically and legally informed care for pregn patients, a holistic view should be taken towards patient's treatment, care and c It is essential to consider individual circumstances of each pregnant cancer pat each patient is seen as a person embedded in the realities of their lives and t that a cancer diagnosis brings to themselves and their pregnancy care.…”
Section: Relationship Between Pregnancymentioning
confidence: 99%
“…The decision to continue the pregnancy should be based on carefully discussing cancer prognosis, treatment, and future fertility with the patient and her partner and the multidisciplinary team. 9 …”
Section: Question 4: How Can We Improve Maternal and Fetal Outcomes I...mentioning
confidence: 99%